The Transiran Railway Project And English-Russian Relations At The Beginning Of The 20th Century (Zien Journal of Social Sciences and Humanities, 2026)
This article details the diplomatic struggle between England and Russia over the construction of the Trans-Iranian railway. The issue of constructing this road has long been an object of geopolitical and geoeconomic interests of Great Britain and Russia. Financial and diplomatic forces were also involved in this struggle. The struggle for large concessions and monopolies in the Middle East became the object of an irreconcilable struggle between the major European powers. This is one of the pages of the "great game" that unfolded at the end of the 19th century in the world's East.